Pentingnya Pengetahuan Pemenuhan Hak Dasar Balita dalam Situasi Darurat Bencana Kebakaran di Wilayah Kerja Puskesmas Maccini Sawah - Nurbaiti Nurbaiti; Ekayanti Hafidah Ahmad; Erna Kasim; Kamaria S. Ahmad; Elawati Pakuku (BADAN PENERBIT STIEPARI PRESS, 2021)
Various disasters that frequently occur in Indonesia have caused various losses and disasters for disaster victims and survivors. This service aims to examine the fulfillment of basic health needs for people who have children under five in the Maccini Sawag Community Health Center Work Area. Questionnaires and interviews were distributed to various stakeholders and the community. Disasters that frequently strike South Sulawesi Province have a high disaster vulnerability index and disasters with a high frequency of occurrence such as: fires, floods and prolonged drought. This activity was carried out on January 14 2021, which was attended by 25 families. The results of the activity show that families think that fulfilling the needs of families with toddlers has been carried out well. Likewise, basic fulfillment indicators such as clothing, food, clean water and sanitation needs, health services, psychosocial services and shelter and shelter have been met well or at least quite well. Various government programs and community participation have also been carried out to ensure that disaster survivors have their health needs met properly.